HPPHM:new policy of store for multidimensional dataset of parallel I/O and research of retrieve performance - CHEN Zhi-gang1; ZENG Bi-qing2 (Tongxin xuebao)
The policy of store and retrieve for large-scale multidimensional dataset was researched.The multidimensional dataset was allocated in the multi-disks among the distributed processing system by using the parallel I/O technology.A new multidimensional data cyclic declustering policy was proposed aiming to data retrieve based on scope by extending existing cyclic policy to multidimensional dataset from adapting to two-dimension,and by using theory analysis on the present method,a new heuristic multidimensional data retrieve policy named HPPHM was proposed.The experimental result has demonstrated the efficiency of new strategy not only in parallel degree but also in robust.